2020
DOI: 10.18038/estubtda.622914
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Characterisation of Asbestos-Free Particulate Ceramic Matrix Composites

Abstract: Production of friction particulate ceramic matrix composites (PCMCs) by powder metallurgy method was carried out using iron 105 μm millscale, 50 μm silica sand, 80 μm magnesia and 53 μm bentonite clay as input materials. Different formulation of the blend of these materials were prepared and the composites were produced. Microstructural, water absorption, and mechanical characterisation were determined using standardised methods. The ceramic composites exhibited very good properties in terms of density, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Figure 10 is a schematic diagram comparing the shear properties of the geopolymers characterized in this study with typical properties found in literature for various materials 26–46 under V‐notch and Iosipescu testing methods.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 10 is a schematic diagram comparing the shear properties of the geopolymers characterized in this study with typical properties found in literature for various materials 26–46 under V‐notch and Iosipescu testing methods.…”
Section: Resultsmentioning
confidence: 91%
“…Low‐tech ceramics, 42 such as silica‐based binders reinforced with iron oxide granules, can reach maximum shear stresses of 5.5 MPa, with further developments recorded up to 6.0 MPa, 43 through a correct tailoring and improved particle bonding up to a 12% content of iron oxide granules. A ceramic fiber–reinforced silica aerogel matrix, 44 however, may present a reduced shear capacity, with only 0.95 MPa in shear stress, mostly due to the deformability of the matrix and the layered feature of the composites. In fact, highly flexible materials, such as polymeric ones, regularly demonstrate minimum shear moduli (less than 1 GPa) and variable shear stresses (from 0.2 to 30 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…This style of formulation is no longer based on steel fibre. It has a stable friction coefficient at widespread temperatures [57]. The construction of the material is very complicated since many materials are used in noise reduction.…”
Section: Parameters Influencing the Friction Materials Formulationsmentioning
confidence: 99%
“…Among these, low-carbon steel is widely used as a metallic fibre due to its exceptional heat stability. Ceramic materials, composed of silica and alumina, also improve wear resistance, insulating properties and high-temperature performance [32,34,49]. The addition of different fibres can lead to diverse behaviours in semi-metallic friction materials concerning tribology.…”
Section: Introductionmentioning
confidence: 99%